2021
DOI: 10.3390/cancers13143616
|View full text |Cite
|
Sign up to set email alerts
|

Risk Score Generated from CT-Based Radiomics Signatures for Overall Survival Prediction in Non-Small Cell Lung Cancer

Abstract: This study aimed to create a risk score generated from CT-based radiomics signatures that could be used to predict overall survival in patients with non-small cell lung cancer (NSCLC). We retrospectively enrolled three sets of NSCLC patients (including 336, 84, and 157 patients for training, testing, and validation set, respectively). A total of 851 radiomics features for each patient from CT images were extracted for further analyses. The most important features (strongly linked with overall survival) were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…With the probability calculated from the above-mentioned algorithm, researchers can turn the answer into a continuous variable to solve regression problems and vice versa. Most AI applications predicting survival [13,59], cancer risk [34][35][36][37][38][39], nodule detection [22,23], and nodule characteristics [33] are based on supervised learning.…”
Section: Supervised Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…With the probability calculated from the above-mentioned algorithm, researchers can turn the answer into a continuous variable to solve regression problems and vice versa. Most AI applications predicting survival [13,59], cancer risk [34][35][36][37][38][39], nodule detection [22,23], and nodule characteristics [33] are based on supervised learning.…”
Section: Supervised Learningmentioning
confidence: 99%
“…Dercle et al retrospectively analyzed the data from prospective clinical trials and found that the AI model based on the random forest algorithm and CT-based radiomic features predicted the treatment sensitivity of nivolumab with an AUC of 0.77, docetaxel with an AUC of 0.67, and gefitinib with an AUC of 0.82 [58]. CT-based radiomics models have also been reported to predict the overall survival of lung cancer [59,60].…”
Section: Medication Selectionmentioning
confidence: 99%
“…These ETs quantify ‘handcrafted (HC)’ features that quantify (i) “semantic features” that describe tumour’s visual characteristics, including tumour shape, size, necrosis and contextual information, such as tumour’s surrounding structures and; (ii) “agnostic features” that quantify statistical information of linear relationships about the pixels of the image that human observers consider important 16 (e.g., colour histograms, Haralick textures and wavelet features 21 , 22 ). Handcrafted ETs have been extensively used to predict mutation status 23 , model cancer outcomes 24 , and response to therapy 13 , 15 . However, handcrafted ETs are restricted to the human understanding of the disease and prespecified imaging representations.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics is an evolving field in medical image quantitative analysis [ 30 ]. It is also known as quantitative image features.…”
Section: Introductionmentioning
confidence: 99%